Purification of Paraoxonase (PON1) from Olive (Olea europaea L.) and Effect of Some Chemicals on Paraoxonase Activity in vitro - Demir, Nazan; Nadaroglu, Hayrunnisa; Demir, Yasar (Asian Journal of Chemistry, 2011)
Paraoxonase was purified from olive (Olea europaea L.) using sepharose 4B-L-tyrosine-1- naphthylamine affinity chromatography. This enzyme was purified 173.4-fold. SDS-polyacrylamide electrophoresis of the enzyme indicates a single protein staining band with an apparent Mr of 45 kDa. The kinetic properties of the purified enzyme were determined. The enzyme exhibited high activity at broad pH (pH 5.0-9.0) and temperature (40 and 70 °C). The purified enzyme remained stable at 4 °C for more than 1 year. Paraoxonase was mostly stable at 40 ºC. Its' activity decreased in 55 % for 1 h at 60 ºC and 20 % for 4 h at 50 ºC. Using paraoxon as a substrate, the Km and Vmax values for the purified enzyme were estimated to be 3.76 mM and 131.5 μmol L dak-1, respectively. The activities were strongly inhibited by Hg2+ and Fe3+, while Cu2+, b-mercaptoethanol, dithioerythritol and SDS slightly activated the enzyme. As judged by catalytic efficiencies, paraoxon is the preferred substrate.